Two Conservative Difference Schemes for the Generalized Rosenau Equation. (8th March 2010) - Hu, Jinsong; Zheng, Kelong
Abstract : Numerical solutions for generalized Rosenau equation are considered and two energy conservative finite difference schemes are proposed. Existence of the solutions for the difference scheme has been shown. Stability, convergence, and priori error estimate of the scheme are proved using energy method. Numerical results demonstrate that two schemes are efficient and reliable.